THE INFLUENCE OF HEDONISTIC STYLE ON THE QUALITY OF LIFE STUDENTS IN MALANG CITY - Azzahra, Fahmida; Radhiyaniputri, Ranayla; Hanzalah, Arafito; Utomo, Hanggara Budi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Globalization that encourages modernization causes significant changes in lifestyle, including the increase in hedonistic lifestyles among students. This hedonistic lifestyle can be a factor that affects the quality of life of students. Method: This study involved 100 participants who were active university students in Malang City. Data was collected using an online survey with google form containing questions using a Likert scale to measure hedonism and students' quality of life. The measuring instruments used were the Hedonic Motivation Scale and WHOQOL-BREF. Results: Data analysis was carried out by conducting reliability tests, validity tests, assumption tests, and simple regression tests. The results of the reliability test with Cronbach alpha are 0.813 on the hedonism lifestyle scale and 0.917 on the quality of life scale, which means that the scale used is reliable because the value is> 0.7. While the validity test results show that reliable items are also declared valid because r count > r table. The results of simple regression analysis show that the hedonism lifestyle has an influence of 17.5% on the quality of life of students. Novelty: This research specifically relates two variables to the context of student life and this research uses a quantitative approach with a simple regression analysis method that provides results on the extent to which hedonistic lifestyles can affect the quality of life of students, this is still rarely discussed in depth in the literature that researchers encounter.